The Washington manual of surgery - Doherty, Gerard M; Eberlein, Timothy J (Lippincott Williams & Wilkins, 2002)
Washington Univ., St. Louis, MO. Brandon/Hill Medical List first-purchase selection (#607). Pocket outline of practical guidelines and algorithms for the management of surgical diseases. Covers pre-surgical evaluation to specific procedures. Previous edition: c1999. Softcover. DNLM: Surgical Procedures, Operative.
Keywords: chirurgie; chirurgie operační; Surgical Procedures, Operative